High-accuracy detection of malaria vector larval habitats using drone-based multispectral imagery - Carrasco-Escobar, Gabriel; Manrique, Edgar; Ruiz-Cabrejos, Jorge; Saavedra, Marlon; Alava, Freddy; Bickersmith, Sara; Prussing, Catharine; Vinetz, Joseph M.; Conn, Jan E.; Moreno, Marta; Gamboa, Dionicia (PLOS Neglected Tropical Diseases, 2019)
Author summary The most efficient malaria vector in the Latin American region is Nyssorhynchus darlingi (formerly Anopheles darlingi). In Amazonian Peru, where malaria is endemic, Ny. darlingi feeds both indoors and outdoors (endophagy, exophagy), depending on the local environment, and rests outdoors (exophily). LLINs and IRS, the most common tools employed for vector control, target endophagic and endophilic mosquitoes. Thus, they are only partially effective against Ny. darlingi. Control of the aquatic stages of vector mosquitoes, larval source management (LSM), targets the most productive breeding sites nearest to human habitation. In four riverine communities, we used drones with high-resolution imagery as a key initial step to analyze water bodies within the estimated flight range of Ny. darlingi, ~ 1 km. We found distinctive spectral profiles for water bodies that were positive versus negative for Ny. darlingi. The methodology and analysis reported here provide the basis for testing whether LSM can be combined successfully with LLINs and IRS to contribute to the elimination of transmission in malaria hotspots in the Amazon.